Juvenile stress induces behavioral change and affects perineuronal net formation in juvenile mice - Ueno, Hiroshi (BMC Neurosci, 2018)
BACKGROUND: Many neuropsychiatric disorders develop in early life. Although the mechanisms involved have not been elucidated, it is possible that functional abnormalities of parvalbumin-positive interneurons (PV neurons) are present. Several previous studies have shown that juvenile stress is implicated in the development of neuropsychiatric disorders. We aimed to clarify the effects of juvenile stress on behavior and on the central nervous system. We investigated behavioral abnormalities of chronically-stressed mice during juvenilehood and the effect of juvenile stress on PV neurons and WFA-positive perineuronal nets (PNNs), which are associated with vulnerability and plasticity in the mouse brain. RESULTS: Due to juvenile stress, mice showed neurodevelopmental disorder-like behavior. Juvenile stressed mice did not show depressive-like behaviors, but on the contrary, they showed increased activity and decreased anxiety-like behavior. In the central nervous system of juvenile stressed mice, the fluorescence intensity of WFA-positive PNNs decreased, which may signify increased vulnerability. CONCLUSION: This study suggested that juvenile stressed mice showed behavioral abnormalities, resembling those seen in neuropsychiatric disorders, and increased brain vulnerability.